VALUE OF 3 TESLA PERFUSION MAGNETIC RESONANCE IMAGING IN PREDICTING HISTOLOGYCAL GRADE AND BIOMARKERS EXPRESSION OF BREAST CANCER (Vietnam Journal of Community Medicine, 2026)
Objective: Analyze the value of perfusion parameters on 3 Tesla magnetic resonance imaging in predicting histological grade, biomarkers expression and molecular classification of invasive ductal breast cancer.Methods: Cross-sectional descriptive study was conducted on 48 patients with invasive ductal breast cancer undergoing magnetic resonance perfusion imaging at the Institute of Diagnostic and Interventional Radiology of Bach Mai Hospital from January 2022 to June 2024. Measure Ktrans, Kep, Ve, Maxslope, CER parameters, collect results of histopathological diagnosis, immunohistochemical staining, and molecular classification. Descriptive statistical analysis and inferential statistical analysis determined the correlation of perfusion parameters with histological grade and expression of biological markers, molecular classification.Results: The Kep parameter can discriminate high and low histology grade with an area under the ROC curve of 0.737. The Ktrans, Kep, Ve parameters have the ability to predict the value of the Ki67 index because Ktrans, Kep have a positive linear correlation with Ki67 while Ve has a negative linear correlation with Ki67 with correlation coefficients are +0.438, +0.373 and -0.326 respectively. Ktrans and CER were capable of distinguishing the HER2-enriched molecular subtype from the remaining groups with an area under the ROC curve of 0.74 and 0.72, respectively.Conclusion: Perfusion parameters on 3 Tesla breast MRI have the ability to predict histology grade and biomarkers expression, molecular classification of invasive ductal breast cancer. Perfusion parameters have the potential to become prognostic factors in breast cancer.
Keywords: Breast cancer, MRI perfusion, ultrafast pulse sequence, quantitative analysis, Ktrans.